Non-IBD immunological diseases are a risk factor for reduced survival in PSC - Rupp, Christian; Mummelthei, Anne; Sauer, Peter; Weiss, Karl Heinz; Schirmacher, Peter; Stiehl, Adolf; Stremmel, Wolfgang; Gotthardt, Daniel (Liver international, 2012)
Abstract: Background: Primary sclerosing cholangitis (PSC) is a chronic cholestatic liver disease. It is known to be associated with immunological diseases (IDs), such as inflammatory bowel disease (IBD) and autoimmune hepatitis (AIH). Aim: We evaluated the presence of IDs be sides IBD and AIH in a cohort of PSC patients, and its association with clinical outcome. Methods: This is a prospective cohort study of 195 PSC patients that were evaluated over the period 1987 – 2010 in ou r tertiary care centre. The presence of ID was determined using a retrospective chart review. IDs were subclassified into autoimmune disease (AID) and immune-mediated inflammatory disease (IMID), according to current guidelines. Results: Twenty-seven of 195 (13.8%) PSC patients had at least one additional ID other than IBD (70%) or AIH (5%). The most frequent AIDs were autoimmune thyroiditis (2.6%) and diabetes mellitus type 1 (2.1%). The most frequent IMIDs were psoriasis (3.6%) and sarcoidosis (2.1%). After more than 20 years of follow-up, concomitant IDs repre sent an independent risk factor for reduced transplantation-free survival in patients with PSC (mean: 8.9 years vs. 16.3 years, P = 0.012). Further subgroup analysis revealed a significantly reduced survival especial ly in patients with concomitant IMID (P = 0.017). Conclusion: Patients with concomitant IDs, especially IMID, are a clinically important subgroup of PSC patients. This significant phenotype warrants further genetic and immunological studies.